Zukunftsfähige Designoptionen für den deutschen Strommarkt : ein Vergleich des Energy-only-Marktes mit Kapazitätsmärkten - Keles, DoganRenz, LeaBublitz, AndreasZimmermann, FlorianGenoese, MassimoFichtner, WolfHöfling, HolgerSensfuß, FrankWinkler, Jenny (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2016)
This study intensively discusses the further developments of the electricity market design in Germany based on substantial scientific insights. For this purpose, an agent-based simulation model is applied to evaluate the operability of the energy only market extended with a strategic reserve. Furthermore, the effects of the implementation of a centralized or decentralized capacity market are analyzed.